Evaluation of Anemia Management and Outcome in ESRF - Elbidiari, Mutwakil Omer Mohammed; Hamid, Abdalwahab Hassan Mohammed (ام درمان, 2016)
Background: The anemia of end stage renal disease (ESRD) is common and often severe complication that affect patient’s quality of life and it is a main cause of mortality, it can be managed successfully by erythropoiesis-stimulating agents (ESA) administration. After recombinant human erythropoietin was introduced into routine nephrology practice, specific clinical guidelines were developed to optimize the quality of anemia management for patients with chronic kidney disease. Although hematocrit values, transferrin saturations, and iron prescription practices have improved over the last years, we sought to determine whether continued opportunities for improvement of this domain of care exist. Objectives: To investigate current practice of anemia management in hemodialysis patients and to assess the appropriateness of anemia management by comparing observed practice to the Kidney Disease Outcomes Quality Initiative (KDOQI) guideline recommendations. Methodology: A random sample of 100 adult in Alakademy Hospital –Hemodialysis facility-HD patients was selected. Dialysis facility staff provided clinical information for the period of September through 30 of January 2016 for (100%) of patients; laboratory information was available returned forms. hemoglobin level, serum ferritin concentrations, erythropoietin dosing, and iron prescriptions were abstracted from patient medical records to assess anemia management practices. Socio-economic information, patients disease history and patient medication history was abstracted. Results: Data were collected from 100 patients. Mean Hb value for those patients was 9.8 g/dl ± 2.1g/dL. twenty-nine patients (29%) had mean Hb values between 11.0 and more, the target range recommended by KDOQI guideline. The mean weekly prescribed dose of erythropoietin was 7800 IU/Week. Information on ferritin concentrations was available for 100 (100%) patients. The mean serrum ferritin concentration for those patients was 990 ± 420.5 ng/mL.thirty (30%) of patients had mean serrum ferritin of less than 500ng/ml which is the maximum level approved by the KDOQI guidelines. Conclusions: There is an opportunity to improve anemia management in hemodialysis patients particularly thorough evaluation of causes of inadequate response rate and better monitoring and management of iron statutes.
Keywords: إدارة مرض فقر الدم -- مرضى غسيل الكلى -- الوقاية والعلاج -- التشخيص السريري -- جودة النتائج -- الرقابة الصحية